2000
DOI: 10.1046/j.1365-2346.2000.00759.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary lipiodol embolism during transcatheter arterial chemoembolization for hepatoblastoma under general anaesthesia

Abstract: We present a case of pulmonary embolism that occurred during the injection of lipiodol during transcatheter arterial chemoembolization under general anaesthesia. A 7-year-old child suffering from a large hepatoblastoma was admitted for arterial chemoembolization and carcinostatic administration. Pulmonary embolism due to lipiodol during arterial chemoembolization was evident by a sudden fall in oxyhaemoglobin saturation from 100 to 90%. This was associated with a spread of lipiodol into both lungs, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Experience with HACE in children is, however, somewhat limited 12–17. The main problem is that chemoembolization is an invasive and technically demanding procedure requiring general anesthesia, and is associated with potential complications 18,19. In this study all four evaluable patients showed response to HACE.…”
Section: Discussionmentioning
confidence: 69%
“…Experience with HACE in children is, however, somewhat limited 12–17. The main problem is that chemoembolization is an invasive and technically demanding procedure requiring general anesthesia, and is associated with potential complications 18,19. In this study all four evaluable patients showed response to HACE.…”
Section: Discussionmentioning
confidence: 69%
“…It is known that a relatively high‐viscosity emulsion is formed by a mixture of Lipiodol and blood, and that the emulsion is retained in the peripheral blood vessels. However, the Lipiodol emulsion is eliminated rapidly due to blood scouring and tissue clearance 35. The elimination results in vascular recanalization, which is one of the key reasons for the poor effect of Lipiodol on permanent embolization of liver tumors ().…”
Section: Resultsmentioning
confidence: 99%
“…Embolization of lipiodol to the lungs may occur through arteriovenous shunting or portovenous shunting. 11 This shunting may not be detectable during TACE. Mild cases of lipiodol embolization may be asymptomatic and discovered incidentally by computed tomography (CT) with high-attenuation areas of lung.…”
Section: Pulmonary Embolizationmentioning
confidence: 99%